2009
DOI: 10.23938/assn.0186
|View full text |Cite
|
Sign up to set email alerts
|

Medical disorders and pregnancy. Gastrointestinal, neurological, cardiovascular and dermatological disorders

Abstract: A pregnant woman can present medical pathologies similar to a woman who is not pregnant. However, the clinical features of some pathologies and the diagnostic or therapeutic process might be altered due to changes produced by pregnancy and the presence of the foetus. In some cases this can limit the diagnostic methods or the therapies to be applied. This article sets out the digestive and cardiovascular pathologies, pathologies of the nervous system and dermatoses of greatest relevance due to their frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several conditions affecting the audio-vestibular system, such as hearing loss, otosclerosis, tinnitus, autophony, facial paralysis, and vertigo, present for the first time or get exacerbated during pregnancy [ 2 ]. This can be explained by the action of estrogen and progesterone on specific structures involved in balance and hearing, such as the cochlea, stria vascularis, and spiral ligament, leading to chemical and osmolar changes in the endolymphatic fluid, which is a critical substance involved in the regulation of inner ear functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several conditions affecting the audio-vestibular system, such as hearing loss, otosclerosis, tinnitus, autophony, facial paralysis, and vertigo, present for the first time or get exacerbated during pregnancy [ 2 ]. This can be explained by the action of estrogen and progesterone on specific structures involved in balance and hearing, such as the cochlea, stria vascularis, and spiral ligament, leading to chemical and osmolar changes in the endolymphatic fluid, which is a critical substance involved in the regulation of inner ear functions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few data have revealed that vertigo is exacerbated in patients with a previous history of Meniere’s disease during pregnancy and some others have reported their onset to be associated with vestibular neuritis; however, there is a lack of information regarding this symptom throughout pregnancy [ 2 ]. Another challenge during this time is the presentation of syncope, unsteadiness, and dysautonomia, which are usually reported by pregnant women, making the diagnosis and follow-up of vertigo even more difficult for clinicians and otolaryngologists.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy can bring about the onset of or exacerbate several audiovestibular system disorders, including autophony, hearing loss, tinnitus, otosclerosis, vertigo, and facial paralysis [2]. It could be described by how estrogen and progesterone affect specific balance and hearing-related structures like the stria vascularis, cochlea, and spiral ligament, which results in osmolar and chemical changes in the endolymphatic fluids.…”
Section: Introductionmentioning
confidence: 99%
“…However, we see that these signs are usually taken less seriously during the childbearing period. A few studies have suggested that vertigo during pregnancy is expressed in those with a history of Meniere's disease, while others have suggested that the beginning of vertigo is related to vestibular neuritis [2]. The occurrence of shakiness, syncope, and dysautonomia during this time, which pregnant women commonly experience, is another challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are multiple symptoms due to the involvement of the audiovestibular system such are hearing impairment, tinnitus, otosclerosis, autophony, facial nerve paralysis, and vertigo present for the first induce or get exacerbated during pregnancy. 2 These audiovestibular manifestations during pregnancy can be explained by the effect of estrogen and progesterone on different structures involved in hearing and balance such as the cochlea, stria vascularis, and spiral ligament, resulting in chemical and osmolar changes in the endolymphatic fluid, which is an important component involved in the regulation of the labyrinthine function. 3 The vestibular symptoms like vertigo or dizziness in pregnant women can affect the mother and child.…”
mentioning
confidence: 99%